Healthcare in the Digital Era – Through the Lens of a Muslim Healthcare Provider - Hasan, Jeffry Abu; Rashid, Aneesa Abdul; Mohamed, Elsa Haniffah Mejia; Daud, Nur Aizati Athirah; Mohamad, Irfan (International Journal of Human and Health Sciences (IJHHS), 2019)
Abstract not available International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 6-7